2022
DOI: 10.3390/molecules28010115
|View full text |Cite
|
Sign up to set email alerts
|

Miglitol, an Oral Antidiabetic Drug, Downregulates Melanogenesis in B16F10 Melanoma Cells through the PKA, MAPK, and GSK3β/β-Catenin Signaling Pathways

Abstract: Hyperpigmentation is a common condition that causes darker spots or patches on the skin, which often look brown, black, gray, red, or pink. This results in unresolved psychological impact due to high anxiety, depression, and somatoform disorder. We aimed to repurpose an antidiabetic drug, miglitol, as an effective compound against hyperpigmentation when applied as a cosmeceutical agent. The present study investigated the antimelanogenic effects of miglitol and the trehalase inhibitor validamycin A. Miglitol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Studies have shown that p38 MAPK is an important intracellular signaling molecule for pigmentation. ERK and JNK are also involved in regulating melanogenesis [ 34 , 35 ]. Several studies have shown that the overall role of MAPK pathway activation in melanin production is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that p38 MAPK is an important intracellular signaling molecule for pigmentation. ERK and JNK are also involved in regulating melanogenesis [ 34 , 35 ]. Several studies have shown that the overall role of MAPK pathway activation in melanin production is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The PKA/CREB signaling pathway plays a critical role in melanogenesis, as PKA can be activated by increased cellular cAMP, which leads to CREB phosphorylation and the subsequent upregulation of MITF transcriptional activity, which results in the expressions of tyrosinase, TRP-1, and TRP-2 [7,8]. To investigate whether 6-methylcoumarin's effect on melanin synthesis is mediated by the PKA/CREB signaling pathway, Western blot experiments were performed to determine whether the PKA and CREB phosphorylation were increased.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to an increase in cAMP levels, which, in turn, upregulates the MITF gene expression. The subsequent increase in MITF protein production positively influences the expressions of TYR and TRPs, which ultimately leads to elevated melanin synthesis [7,8]. Furthermore, the MAPK family proteins can increase MITF expression and the subsequent expression of melanogenesis enzymes in a similar fashion.…”
Section: Introductionmentioning
confidence: 99%
“…The field of cosmeceuticals targeting the skin is no exception: skin appearance is essential for self-esteem and quality of life, and therefore skincare products represent a huge market. In particular, cosmeceuticals are a hybrid category of skin care formulations that are halfway between cosmetics and pharmaceuticals and are rationally designed to target (pathological) physiological mechanisms to improve skin health and appearance [28][29][30].…”
Section: Discussionmentioning
confidence: 99%